Rural Women Transforming: Tools for Empowerment - Albornoz Arias, Neida Coromoto; Rojas Sanguino, Camila Andrea; Santafé Rojas, Akever Karina (2024)
This document corresponds to a Toolbox based on methodologies for the empowerment of rural women in the Catatumbo region, product of the research project: “Value proposal in the cocoa production unit(s) of rural women, to overcome the barriers they face along the production chain, through individual and collective empowerment, in the municipalities of Tibú and Sardinata, Department of Norte de Santander, Colombia”. Project funded by the Ministry of Science, Technology and Innovation (MINCIENCIAS). [Code 102882 CT 235-2023]. Call 935. Orchids Programme. Women in Science: Agents for Peace, executed by the University of Pamplona.This product corresponds to a Toolkit that has been made possible thanks to the support and collaboration of a group of rural women, both in the municipality of Tibú and Sardinata, Norte de Santander, Colombia. Through their participation in the fieldwork sessions, they laid the foundations for the development of this product, whose purpose is to provide practical resources, knowledge and skills that promote the strengthening of women's capacities to influence their personal, family and community environments. This document contains the Decalogue of Rural Women's Teamwork, Methodologies for Strengthening Individual Empowerment, Methodologies for Strengthening Collective Empowerment and Methodologies for Sustainability and Territorial Development.
Keywords: Rural women; Empowerment; Self-esteem; Leadership; Digital skills; administrative sanctioning procedure